Beneficial impact of a mix of dairy fat with rapeseed oil on n‐6 and n‐3 PUFA metabolism in the rat: A small enrichment in dietary alpha‐linolenic acid greatly increases its conversion to DHA in the liver. Issue 3 (29th October 2014) - Ezanno, Hélène; Beauchamp, Erwan; Catheline, Daniel; Legrand, Philippe; Rioux, Vincent
<x xml:space="preserve">Abstract</x> The impact of the amount of dietary α‐linolenic acid (ALA) on its own tissue accumulation and conversion to longer n‐3 polyunsaturated fatty acids (PUFAs) remains controversial and may depend on the other dietary fatty acids mixed with ALA. Whereas linoleic acid (LA) is well known to compete with ALA for its conversion to longer n‐3 PUFAs, the concomitant presence of dietary ALA with dairy saturated fatty acids (C4:0–C14:0) that are highly susceptible to β‐oxidation may inversely lead to its increased cellular storage and better conversion to long‐chain n‐3 PUFAs. The present study was therefore aimed at investigating further the putative beneficial effect of dietary dairy fat on n‐3 PUFA tissue levels in the rat. Firstly, we showed that when combined with a well‐defined dietary level of ALA (0.6% energy), substitution of olive oil for butterfat improved ALA storage in adipose tissue and liver, and had moderate effects on its conversion to n‐3 long‐chain PUFAs. Secondly, we showed that, when mixed with dairy fat, a small increase in dietary ALA (from 0.6 to 0.8% of energy) enhanced the ALA storage in adipose tissue only but conversely significantly increased its conversion to highly unsaturated n‐3 PUFAs in the liver. Practical applications: α‐linolenic acid (ALA) is the most accessible source of n‐3 PUFAs in the global diet. However, the intake of ALA is currently lower than dietary guidelines and the rate of ALA conversion to longer chain n‐3 PUFAs is low. The results from this study showed that a small enrichment in dietary ALA combined with dairy fat increased adipose tissue ALA storage, which represents a slow releasable pool that may be utilized over time by other tissues and greatly increased the conversion of ALA to highly unsaturated n‐3 PUFAs in the liver. This knowledge may possibly result in the development of new dietary strategies to increase the cellular level of n‐3 PUFAs in animals and humans. <inline-graphic xlink:href="ark:/27927/pgj983crrx" content-type="ejlt201400304-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> When mixed with dairy fat, a small increase in dietary α‐linolenic acid (from 0.6 to 0.8% of energy) enhances the α‐linolenic acid storage in adipose tissue and significantly increases its conversion to highly unsaturated n‐3 polyunsaturated fatty acids in the liver.